2004
DOI: 10.1002/neu.20071
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated expression of c‐Fos and c‐Jun in the brainstem auditory nuclei of Gallus domesticus is modified by prenatal auditory enrichment

Abstract: Recognition of mother's voice by human neonates and behavioral responses of birds and animals to sounds experienced prenatally emphasize the role of sensory inputs in auditory system development. Spontaneous and experience driven neural activity influence the neural circuits' refinement in developing brain. However, cellular mechanisms endowing plasticity for such structural refinement during critical developmental periods are less understood. Sensory stimulation induces fluctuating expression of transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
(43 reference statements)
1
13
0
1
Order By: Relevance
“…Moreover, phasic alterations of Ca 2+ i mediate the expression of K + channels that modulate SAPs, or influence the gene expression that may refine neuronal connections [26][30]. 4-AP-sensitive currents, presumably of A-type K + currents (I A ) regulate spike timing and firing frequency in neurons [31][33] and cardiac myocytes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phasic alterations of Ca 2+ i mediate the expression of K + channels that modulate SAPs, or influence the gene expression that may refine neuronal connections [26][30]. 4-AP-sensitive currents, presumably of A-type K + currents (I A ) regulate spike timing and firing frequency in neurons [31][33] and cardiac myocytes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Since developing neurons with more contacts succeed in engaging an axon to the soma to ultimately survive (Jhaveri and Morest, 1982), it is likely that more number of postsynaptic neurons survive following auditory stimulation. We also showed that extra‐sensory stimulation modulated the developmental expression of transcription factors, c‐Fos and c‐Jun; c‐Fos protein showed a gradual age‐ and stimulus‐dependent increase in expression, parallel to the enhanced syntaxin1 expression (Alladi et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…The enhanced sound stimulation favors the survival of neurons by reducing physiological cell death and increasing the relative amounts of Bcl-2, a anti-apoptotic protein (Alladi et al, 2005a). Prenatal patterned acoustic stimulation enhances synaptic protein synthesis (Alladi et al, 2002) and modulates the expression of the immediate early gene products, c-Fos and c-Jun, in NM and NL (Alladi et al, 2005b). Furthermore, the sound-stimulated groups show an increase in neuronal size and the proportion of neurons containing calcium-binding proteins (CaBPs)-calbindin D-28K (CALB) and parvalbumin (PV) in the mediorostral nidopallium hyperpallium ventrale (MNH), which is an auditory imprinting area of chick forebrain (Panicker et al, 2002).…”
Section: Introductionmentioning
confidence: 98%